Sacral neuromodulation for faecal incontinence - K.E. Matzel; B. Bittorf (Continence)
Sacral neuromodulation (SNM) is an established, highly relevant, surgical therapy for faecal incontinence (FI). The spectrum of indications has evolved over time. Currently, these include a wide variety of pathophysiological and pathomorphological causes. However, they can extend beyond the exclusively faecal to include complex conditions such combined faecal and urinary dysfunction and low anterior resection syndrome (LARS). To improve the outcome of SNM further, crucial elements of the therapy such as electrode placement have been refined and standardized. This article addresses the scope of indications, highlights the results and the role of SNM in the treatment armamentarium of FI, and touches upon current trends.